PM Modi and foreign policy - Rai, Ashok kumar (New Delhi Oxford, 2023)
About Prime Minister Modi is an Indian politician serving as the 14th and current Prime Minister of India since 2014 and discus about foreign policy of Indian government.
Keywords: Prime Minister; Foreign policy